Estimation of gillnet selectivity for Tor tambra captured in Lirik River, Merangin Regency, Jambi Province - Muhammad Natsir Kholis; Sulaeman Martasuganda; Mohd. Yusuf Amrullah; Jaliadi Jaliadi (Tomini Journal of Aquatic Science, 2020)
Fishing gear selectivity is the condition of a fishing gear that can catch fish the target of catching and escaped other fish so that selectivity has an essential role for fisheries managers who make regulations regarding the mesh size. The purpose of this study is to estimate the selectivity of gillnet fishing gear on Semah fish (Tor tambra). The method used in this research is the experimental fishing method. The results showed that the gillnet in the Lirik river has an estimated value of selectivity to Semah fish (Tor tambra) mesh size of 1.5 inches at a length of 48.59 cm and a mesh size of 2 inches at a length of 64.78 cm. Semah fish (Tor tambra) which have a length far below the estimated value of selectivity will be able to pass through the net without getting caught (escaped), and fish that have a length far above the estimated value of selectivity will be entangled.